Racism In French Rap Songs (Booba and Black M) - Chintya Aprilia; Yuli Mahmudah Sentana; Indah Nevira Trisna (Lingua Litteria Journal, 2026)
This study aims to identify racism in the songs "Je Suis Chez Moi" by Black M, "Ma Couleu" by Booba, and "Pitbull" by Booba. This study uses the subaltern theory by Gayatri Chakravorty Spivak. This study uses a qualitative descriptive method. The data in this study consist of words, phrases, or sentences in songs that contain racist elements. Data collection techniques included listening and note-taking. The results of the study on these three songs indicate that racism against immigrants is still widespread. Immigrants remain subaltern in society, and discrimination continues to occur. Racism in these songs is divided into two: skin color racism and structural racism. Black skin seems to be the absolute reason why this racism occurs. However, other forms of racism refer to the difficulty of accessing employment and social injustice. These three songs show how the subaltern is depicted through immigrants and descendants of immigrants in their lives in the banlieue and the racism they have to face every day.